Knowledge, Attitudes and Practices (KAP) toward seasonal influenza vaccine among young workers in South China - Yu Ma; Tiegang Li; Wanqi Chen; Jiandong Chen; Meixia Li; Zhicong Yang (Human Vaccines & Immunotherapeutics, 2018)
Background: Vaccination against seasonal influenza is usually very protective. However, coverage in service workers is low due to the large population density and high turnover. The aim of this study was to document the knowledge, attitudes and practices towards the influenza vaccine among young service workers. Methods: A face-to-face interview and questionnaire were administered at the Guangzhou Center for Disease Control and Prevention (GZCDC) clinic. The questionnaires were analyzed to evaluate knowledge, attitudes and willingness to vaccinate in the service industry population. Results: Overall, the response rate was 81.37% (1035/1272). Most of the participants had faith in the efficacy (94.20%) and safety (94.88%) of the influenza vaccine. A total of 88.7% of the respondents confirmed that children needed to be vaccinated compared to other subjects, including those who work with baby and children (45.89%), elderly people (38.95%), medical staff (38.95%) and chronic disease patients (27.33%). Only 6.47% of the respondents were clearly aware of the vaccination timeframe. One-fifth of the respondents (18.16%) reported being vaccinated within the last three years, representing a low voluntary vaccination rate (23.94%) and a high irregular vaccination rate (77.13%). The primary reason for ignoring the importance of vaccination was that the respondents believed that they were strong enough to not require immunization (42.19%). In the multivariate analysis, the main determinants of the participants' willingness to continue to vaccinate were their beliefs in vaccine protection, a high education level, vaccination behavior over the last 3 years and belief in the necessity of annual vaccinations. Conclusion: Our findings provide insights into the knowledge, attitudes and practices of the service industry population prior to vaccination season in Guangzhou City. Most participants had a passive attitude toward the influenza vaccine, but there was still relatively low knowledge and implementation of the vaccine. Governments and health departments at all levels should develop a long-term strategy for fiscal subsidy policies and new health education patterns to enhance both the recognition and coverage of the influenza vaccine and to protect the citizens as a whole from infection. There is an urgent need for the pharmaceutical industries to develop a universal vaccine and to enhance the efficacy of vaccination.